A new species of Amazophrynella (Anura: Bufonidae) with two distinct advertisement calls - Kaefer, Igor Luis; Rojas, Rommel R.; Ferrão, Miquéias; Farias, Izeni Pires; Lima, Albertina Pimentel (Zootaxa, 2019)
Here we describe a new species of the toad genus Amazophrynella (Bufonidae) from the south margin of the Amazon River in Santarém, state of Pará, Brazilian Amazonia. The new species can be diagnosed by (1) medium body size for the genus: adult females 19.5–20.4 mm SVL, adult males 13.0–14.5 mm SVL; (2) snout acuminate in lateral view; (3) Finger I larger and robust; (4) Finger I nearly equal in size than Finger II; (5) palmar tubercle rounded, covering ¼ of hand; (6) pigmented callus in Finger I in males; in life: (7) brown stain on throat and chest; (8) black dots on venter. Males emit two distinct advertisement calls: the call type 1 consists of a relatively long note (mean 0.248 s) with a mean dominant frequency of 3526 Hz. The call type 2 is arranged in bouts of 6 to 22 notes with mean dominant frequency of 3450 Hz and much shorter note durations (mean 0.034 s). In this study we also redescribe the advertisement call of A. minuta, which also emits a second call type.